Coordinates of efficiency / inefficiency in raising sheep - Rodica Chetroiu; Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper highlights coordinates and aspects of the sheep breeding sector, which can lead to the creation of the framework of efficiency or inefficiency of production activities. The sheep sector is very diverse in terms of farm size, breeds and scale of production. Low average incomes, which limit investment in the sector and are not attractive to potential younger entrants, low modernization thresholds, infrastructure weaknesses, lack of training or a product marketing strategy are challenges for the sector. On the other hand, local market opportunities may arise from rural tourism, such as direct sale of products to those who value traditional quality products. Positive aspects can also arise from the sector's capacity to provide environment advantages: as the animals from this sector are grown mainly in extensive systems, they play a key role in landscapes and biodiversity conservation. The positive annual average rates of the last 10 years in Romania regarding the increase of sheep (+ 2.4%) and the increase of sheep meat production (+ 1.91%) indicate an upward trend of activities towards the production of sheep meat, in parallel with a slightly downward slope (-0.43% average annual rate) in the direction of milk production.
Keywords: O12; O13; Q12; 330; efficiency; sheep; meat; milk